Elucidation of Performance Recovery for Fe‐Based Catalyst Cathodes in Fuel Cells. Issue 12 (8th October 2021) - Beltrán, Diana E.; Uddin, Aman; Xu, Xiaomin; Dunsmore, Lisa; Ding, Shuo; Xu, Hui; Zhang, Hanguang; Liu, Shengwen; Wu, Gang; Litster, Shawn
Abstract : Platinum group metal (PGM)‐free oxygen reduction reaction (ORR) catalysts for proton exchange membrane fuel cells (PEMFCs) continue to demonstrate significant advances in catalytic activity. Unfortunately, the most promising catalysts exhibit initial rapid activity loss as well as significant sustained activity decay. Herein, it is shown that PGM‐free cathode fuel cell performance can be partially recovered by an in situ electrochemical method by restoring a percentage of the original active sites or activating originally inactive sites. The same approach is also shown to increase the initial activity if applied to a pristine PGM‐free cathode. This is achieved by applying low constant potential holds to the cathode in the absence of oxygen in the cathode, by either flowing nitrogen or blocking the delivery of air and removing the residual oxygen by the ORR. Two types of active sites are further differentiated with degradation mechanisms characterized by different populations and timescales. It is hypothesized that the recovery of sites is due to the reduction of Fe 3+ to Fe 2+, restoring a percentage of the original active sites or activating originally inactive sites. This reduction has additionally shown to generate the removal of oxygen adsorbates at the catalyst surface. Abstract : Approaches to recover iron (Fe)‐based catalyst performance during fuel cell operation is achieved by applying low voltages while starving the cathode of oxygen. Recovery is likely due to the reactivation of once deactivated sites or activation of originally inactive sites. The possibility of recovery can introduce durable high‐power density platinum group metal (PGM)‐free cathode fuel cells.